Immunity to East Coast fever in cattle induced by a polypeptide fragment of the major surface coat protein of Theileria parva sporozoites - Bishop, Richard P.; Nene, Vishvanath M.; Staeyert, J.; Rowlands, G.J.; Nyanjui, J.; Osaso, J.; Morzaria, S.P.; Musoke, A.J. (Elsevier, 2003)
Full-length recombinant versions of p67, the 709 amino acid major surface protein of Theileria parva sporozoites, induce immunity to East Coast fever (ECF) in cattle. We show that a soluble Escherichia coli recombinant version of p67 (p67635), in which a prokaryotic signal peptide replaces the eukaryotic one, confers protection comparable to that induced by the full-length molecule, but is unstable. Peptides encoding 80 (p67C) and 205 (p67N) amino acid fragments of p67, containing epitopes recognised by sporozoite neutralising monoclonal antibodies, exhibit improved stability in E. coli. Antibodies raised against the central region of p67 (p67M) neutralise sporozoite infectivity in vitro. The p67C peptide induced immunity against ECF in cattle, at a level equivalent to p67635, suggesting that a synthetic peptide vaccine might be achievable.